Management of Isolated Anal Strictures in Crohn's Disease. Issue 12 (December 2020) - Lightner, Amy L.; Click, Benjamin; Yamamoto, Takayuki; Spinelli, Antonino; Kotze, Paulo
Abstract : BACKGROUND: Anorectal stricturing is a particularly morbid manifestation of Crohn's disease resulting in a diminished quality of life related to pain, incontinence, and recurrent operative interventions. OBJECTIVE: To determine the role of medical therapy, endoscopic dilation, and surgical intervention for the treatment of isolated anorectal stricturing. DATA SOURCES: An organized search of MEDLINE, PubMed, EMBASE, Scopus, and the Cochrane Database of Collected Reviews was performed from January 1, 1990 through May 1, 2020. STUDY SELECTION: Full text papers which included management of isolated anorectal strictures in the setting of Crohn's disease. INTERVENTION(S): Medical and surgical management. MAIN OUTCOME MEASURES: Symptomatic relief, need for proctocolectomy. RESULTS: Our search identified a total of 553 papers; after exclusion based on title (n = 430) and abstract (n = 47), 76 underwent full text review with 65 relevant to the management of anorectal strictures. A summary of the retrospective reports suggests that medical therapy can help control luminal inflammation, but fibrosis may ultimately set in resulting in a need for endoscopic or surgical intervention. Surgical options are limited in the anal canal due to inflammation and ulceration and concomitant perianal fistulizing disease. While fecal diversion can provide symptomatic relief, successful restoration of intestinal continuity remains uncommon and most patients ultimately undergo a total proctocolectomy with end ileostomy. LIMITATIONS: Limited literature published, all retrospective in nature. CONCLUSIONS: Despite significant advances in medical and surgical therapy in Crohn's disease over the last decades, there is clearly an unmet need in the management of anorectal strictures in Crohn's disease.